2006
DOI: 10.1159/000092536
|View full text |Cite
|
Sign up to set email alerts
|

Increased Aortic Intima-Media Thickness Is Related to Lipid Profile in Newborns with Intrauterine Growth Restriction

Abstract: Background and Aim: Low birth-weight is known to be associated with an increase in cardiovascular risk similar to that seen with major environmental risk factors, such as cigarette smoking or hypertension. Much epidemiological evidence has linked low birth-weight with hypertriglyceridaemia. Method: We measured aortic wall thickness by ultrasonography and lipid profile in 40 newborn babies with intrauterine growth restriction and 40 controls. Results: Maximum and mean aortic intima-media thickness were signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
66
3
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 31 publications
10
66
3
2
Order By: Relevance
“…21 Moreover, our reported arterial layer thicknesses are much thinner than those previously reported, indicating an important difference in methodology attributable improved axial resolution, as recently discussed. 26 However, our results may not be directly comparable to the studies by Skilton et al, 13 Koklu et al, 14 Gunes et al, 15 Koklu et al, 16 Cosmi et al, 17 and Zanardo, 18 as these examined the aorta and not the carotid, brachial, or femoral Femoral artery lumen diameter, intima-media thickness, and intima-media-adventitia thickness in relation to gestational age and body surface area in large for gestational age (blue), small for gestational age (red), and appropriate for gestational age (white) neonates. Layers were below resolution in the smallest neonates as indicated by the lack of data at the level of <0.05 mm.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…21 Moreover, our reported arterial layer thicknesses are much thinner than those previously reported, indicating an important difference in methodology attributable improved axial resolution, as recently discussed. 26 However, our results may not be directly comparable to the studies by Skilton et al, 13 Koklu et al, 14 Gunes et al, 15 Koklu et al, 16 Cosmi et al, 17 and Zanardo, 18 as these examined the aorta and not the carotid, brachial, or femoral Femoral artery lumen diameter, intima-media thickness, and intima-media-adventitia thickness in relation to gestational age and body surface area in large for gestational age (blue), small for gestational age (red), and appropriate for gestational age (white) neonates. Layers were below resolution in the smallest neonates as indicated by the lack of data at the level of <0.05 mm.…”
Section: Discussioncontrasting
confidence: 82%
“…[13][14][15][16][17][18][19][20] Our findings are inconsistent with studies reporting an increase in arterial wall layer thickness in LGA neonates 26,27 but in concordance with previous autopsy studies on SGA neonates. 21 Moreover, our reported arterial layer thicknesses are much thinner than those previously reported, indicating an important difference in methodology attributable improved axial resolution, as recently discussed.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…In addition, increased cholesterol deposition in foetal aortas could give rise to exaggerated lipid-rich lesions in both aortic arch and abdominal aorta in children (Napoli et al, 1997(Napoli et al, , 1999. These observations correspond to the 'foetal origins hypothesis', which states that an unfavourable intrauterine metabolic environment predisposes for premature cardiovascular disease (Koklu et al, 2006;Skilton, 2008).…”
Section: Introductionsupporting
confidence: 56%
“…Although the clinical complications of atherosclerosis occur in adult life, the process of atherogenesis begins in childhood (4). In our previous study (5), we found that newborn babies with growth restriction had significant aortic thickening with hypertriglyceridemia.…”
mentioning
confidence: 78%